Perancangan Pompa Hidram Head Rendah Menggunakan Pemograman Visual Basic - Muhammad Ilham Maulana (Jurnal Teknik Mesin Unsyiah, 2013)
A hydraulic ram pumps, or shortly known as a hydram, is a water-lifting device that operates automatically and continuously. It is a device that uses the energy in the flowing water such as spring, stream or river to pump part of the water to a height above that of the source. With a continuous flow of water a hydram operates continuously with no external energy source. Hidram pump design influenced several input parameters such as head, inlet pipe diameter and yield parameters: length of inlet pipe, heavy weight exhaust valve, the inflow speed, output flow rate and efficiency of the pump. In this study, the analysis is done using visual basic 6.0 computer program, as well as completion of the problem in terms of design of the hydram pump. The performance results are then compared with the experimental results. This program aims to ensure that everyone can design and make the hidram pump, with still follow the general rules of the proper design.